THE INFLUENCE OF CASH TURNOVER, RECEIVABLES TURNOVER, AND WORKING CAPITAL TURNOVER ON PROFITABILITY IN CONSTRUCTION AND BUILDING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE 2018-2022 - Nurfazila; Rico Nur Ilham; Ghazali Syamni; Marzuki (Universitas Efarina, 2023)
This research aims to analyze the effect of cash turnover, accounts receivable turnover and working capital turnover on profitability in construction and building subsector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This research uses secondary data obtained from the financial reports of construction and building companies selected using a proportional sampling technique. The sample chosen was 20 construction and building companies and had 100 observations. The estimation model for this research uses panel data regression analysis with the Random Effect Model. The results of this research show that cash turnover has a positive but not significant effect on profitability. This can mean that cash turnover is managed well and effectively so that it can increase profits, but statistically it is not strong enough to be concluded as a definite or consistent relationship. The results are the same. shows that the results of receivables turnover have a positive and insignificant effect on profitability, although there is a positive influence between how quickly the company collects receivables and the effectiveness of using assets in generating profits, the effect is not strong and consistent enough to be considered statistically significant. Different results were found that working capital turnover had a negative and insignificant effect on profitability. This means that when working capital turnover increases, profitability tends to decrease.